Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00330-015-3885-y
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer detection rates using four different types of mammography detectors

Abstract: Objectives To compare the performance of different types of detectors in breast cancer detection. Methods A mammography image set containing subtle malignant non-calcification lesions, biopsy-proven benign lesions, simulated malignant calcification clusters and normals was acquired using amorphous-selenium (a-Se) detectors. The images were adapted to simulate four types of detectors at the same radiation dose: digital radiography (DR) detectors with a-Se and caesium iodide (CsI) convertors, and computed radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…The results demonstrated that the doses for the standard beast were satisfactory and in most cases within the reference levels of 2.5 mGy [2], when analyzed without taking into account the image quality. In particular, the presented results related to CR systems reflecting the necessity to establish procedures for optimisation that require the participation of a medical physicist, radiographers, radiologists and field engineers of both x-ray mammography equipment and CR system used as image receptors [10][11][12]. The physical measures expressing spatial resolution and signal-to-noise ratio are consistent with the published finding that sites employing CR systems had lower image quality [13].…”
Section: Discussionsupporting
confidence: 84%
“…The results demonstrated that the doses for the standard beast were satisfactory and in most cases within the reference levels of 2.5 mGy [2], when analyzed without taking into account the image quality. In particular, the presented results related to CR systems reflecting the necessity to establish procedures for optimisation that require the participation of a medical physicist, radiographers, radiologists and field engineers of both x-ray mammography equipment and CR system used as image receptors [10][11][12]. The physical measures expressing spatial resolution and signal-to-noise ratio are consistent with the published finding that sites employing CR systems had lower image quality [13].…”
Section: Discussionsupporting
confidence: 84%
“…A virtual clinical trial [10] examined the use of four different types of mammography detector to detect inserted calcification clusters and real non-calcification lesions and is referred to here as the 4-detector observer study. In that trial a set of cases with calcification clusters and malignant non-calcification lesions was prepared and the images converted to appear as if acquired on four different types of detector using methods previously described [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…The observer study [10] used one view (either CC or MLO) of both breasts from 269 cases including normal images (80 cases) and images with non-calcification lesions (80 cases), inserted calcification clusters (80 cases) and biopsy-proven benign lesions (29 cases). The study protocol was approved by the regional research ethics committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations